Penentuan Daya Cerna Protein In Vitro Ikan Bawal (Colossoma Macropomum) pada Umur Panen Berbeda - Saputra, Dede (ComTech: Computer, Mathematics and Engineering Applications, 2014)
Digestibility is part of the sample consumed and not released into the feces. This study discusses about the protein digestibility of tambaqui fish (Colossoma macropomum) at different ages and sizes in vitro. Protein digestibility is the ability of the organisms to break down proteins into simple molecular compounds. At the initial stage, all samples used were dried, then distilled water at pH 8 added, and later the mixture was homogenized for three minutes. After the mixture was homogeneous, enzymes and distilled water were added. Samples were then centrifuged and the absorbance of the sample was measured using absorption spectrophotometry. The results obtained during the observations showed that the digestibility of proteins in the casein showed a value of 100%, small pomfret fish for 28.37%, pomfret fish at 58.42%, and large pomfret fish amount to 88.39%. This shows the larger size of the fish, then the digestibility of protein will be higher. In addition, the lower the pH, the protein digestibility will be higher for hydrolysis of proteins requires an acidic environment of pH conditions.